The love of money ([Australia] : BBC, 2009)
In September 2008, capitalism looked like it was on the brink of collapse. This is the story of how the crash was caused, what happened, and how generations to come will be affected by its legacy. Part one examines when the collapse of Lehman Brothers plunged the world into financial crisis and part two examines the boom years before the global financial crash of 2008
ep.1.- The bank that bust the world / directed by Guy Smith ep.2 .- The age of risk / directed by Tim Robinson
Narrator, Alex Jennings.
DVD format
In English with optional captions in English.
Keywords: Global Financial Crisis, 2008-2009; Financial crises -- United States -- History -- 21st century; Business failures -- United States -- History -- 21st century; Investment bankers